Rhizopus rhizopodiformis: emerging etiological agent of mucormycosis. - Bottone, E J (1979)
Mucormycosis is caused principally by members of the genus Rhizopus, especially R arrhizus and R. oryzae. Infection attributable to R. rhizopodiformis has rarely been documented. Of 13 cases of mucormycosis diagnosed during a 4-year period (1974 to 1978) at The Mount Sinai Hospital, 6 cases, occurring within 9 months, were caused by R. rhizopodiformis. The six isolates were identified mainly by: growth at 50 degrees C; production of short, sometimes branched, sporangiophores arising from opposite rhizoids; elongated columellae; and small spherical-to-elliptical, smooth-to-finely striated sporangiospores. The possibility that this explosive occurrence of R. rhizopodiformis at our institution was because of nosocomial acquisition was strongly supported by the recovery of this same mycotic agent from adhesive bandages used in the cardiac intensive care unit, where a patient developed subcutaneous R. rhizopodiformis infection after cardiac surgery. The invasive potential of R. rhizopodiformis was manifested by the extensive subcutaneous and systemic infections in each of the six patients, three of whom developed antibody against this mucormycotic agent.